2020
DOI: 10.1177/0192513x20918393
|View full text |Cite
|
Sign up to set email alerts
|

MMPI-2 Profiles of Mothers Engaged in Parental Alienation

Abstract: Parental alienation (PA) describes a family dynamic in which a parent engages in behaviors that are likely to foster a child’s unjustified rejection of the other parent. PA is considered a particular form of child psychological maltreatment with both short- and long-term negative consequences. Parents who attempt to turn a child against the other parent in cases of separation/divorce can be difficult to identify. Increasing our understanding of the personality features of these parents via psychological assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Our data suggests that these characteristics were the strongest predictors of alienating behaviors. These results are in line with the previous study by Roma et al (2020a), which found that mothers classified as alienating showed psychological profiles characterized by a high selffavorable bias (i.e., a tendency to present an image of adequacy and self-control that is incompatible with real life), rigid moral values, greater sensitivity to criticism, susceptibility to others' behaviors, and a tendency to deny negative dispositions in others.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data suggests that these characteristics were the strongest predictors of alienating behaviors. These results are in line with the previous study by Roma et al (2020a), which found that mothers classified as alienating showed psychological profiles characterized by a high selffavorable bias (i.e., a tendency to present an image of adequacy and self-control that is incompatible with real life), rigid moral values, greater sensitivity to criticism, susceptibility to others' behaviors, and a tendency to deny negative dispositions in others.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, they had a greater tendency to deny faults and complaints (K scale), and they were more likely to exaggerate their benevolence and morality (S scale). These results were recently confirmed by research on mothers' MMPI-2 personality traits in 58 parental alienation cases (Roma et al, 2020a).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…On the one hand, it is necessary to determine the child's psychological development, and on the other hand, it is necessary to identify the presence of behavioral problems and psychological developmental disorders so that early education, early intervention, and early treatment can be targeted [4][5]. There are many types of psychological assessments for young children, which are divided into cognitive, such as perceptual, language tests, emotional-behavioral assessments, aptitude tests, and personality tests according to the psychological domains involved [6][7][8]. They are divided into interview, observation, test, and questionnaire methods according to the form of assessment, screening, and diagnostic assessments according to the accuracy of the assessment, and textual and non-textual test materials.…”
Section: Background Of the Studymentioning
confidence: 99%
“…If we set the joint control domain of the elementary variables to be and take the significant level in the control process, the relationship between the significant level and the control domain is satisfied as follows: (7) The normal distribution has symmetry and its distribution density is equal everywhere on the boundary of the control domain . Thus when the significant level is determined, the variation is: (8) Where is the constant corresponding to . Bringing equation (7) into equation ( 8), we get:…”
Section: Psychological Assessment Of Young Childrenmentioning
confidence: 99%